Not One but Many "Moravian Churches": Towards a Plural Turn in Moravian Studies - Leemann, Michael (Exchange, 2025)
Building on recent research in early modern Moravian history, this article introduces the term "Moravian Churches" to emphasise the diversity of the Moravian Church. Scholars of Moravian studies usually underline the group cohesion of a single global "Moravian Church". Drawing on concepts such as the "network", they privilege the cohesiveness of Moravians over the considerable inner-Moravian plurality. By contrast, this contribution explores how the global Moravian Church was a community that comprised distinct Moravian Churches. Indeed, by examining church discipline in the Moravian mission to the Black enslaved people in the Danish West Indies, it highlights the Moravians’ entanglement with the surrounding slave society. Moreover, White eighteenth-century Moravians themselves stressed that the Danish West Indian Moravian Church was dependent on several different centres, further highlighting the significance of polycentricity as an analytical tool in the study of religious plurality.